Proton mediated spin state transition of cobalt heme analogs - Jianping Zhao (Nature Portfolio, 2019)
Studying the electronic structures and spin transitions of synthetic heme analogs is crucial to advancing our understanding of heme enzyme mechanisms. Here the authors show that a Co(II) porphyrin complex undergoes an unexpected spin state transition upon deprotonation of its axial imidazole ligand.